Entrepreneur training needs analysis : implications on the entrepreneurial skills needed for successful entrepreneurs. - Jusoh, Rosnani; Ziyae, Babak; Asimiran, Soaib; Abdul Kadir, Suhaida (2010)
This paper is one of the outcomes of the study from interview of 30 entrepreneurs in Malaysia, investigating the business competencies needed for successful in their business. In the paper, the training needs of entrepreneurs are identified and analysed with respect to a number of issues affecting business such as creativity and innovation, sources of business finance, accounting skills, financial management, areas in which the entrepreneurs find it difficult to acquire knowledge. The study confirm the view of entrepreneurship education makes a significant different in the performance of entrepreneurs, with entrepreneurs expressing a need for further training and education in specific business issues.